Training and evaluation of professional competency in pediatric nursing: perspective of university professors - Garcia Regino, Daniela da Silva; Garcia Nascimento, Juliana Da Silva; Garcia De Lima Parada, Cristina Maria [UNESP]; Cassamassimo Duarte, Marli Teresinha [UNESP]; Pamplona Tonete, Vera Lucia [UNESP] (Univ Sao Paolo, 2019)
Objective: To analyze the training and evaluation of professional competency to work in the area of pediatric nursing based on the conceptions and experiences of university professors. Method: A qualitative study conducted with pediatric nursing professors from six public undergraduate courses in the state of Sao Paulo, Brazil. The data were collected by semi-structured interview and analyzed by the Content Analysis method. Results: Sixteen professors participated. Five main themes emerged: competency definition, attributes to act with children, advances in the training of professional competency, challenges to enable training pediatric competency, and methods and instruments for evaluating competency acquisition to work in the area of pediatric nursing. Conclusion: The findings of this study point to the importance of a balanced approach in the cognitive, psychomotor and affective dimensions in training and evaluating professional competency in pediatric nursing, as well as extending the curricular valorization of this area of knowledge and practice.
Keywords: Pediatric Nursing; Education; Nursing; Competency-Based Education; Educational Measurement